Utilization of fermented sago pulp as a source of carbohydrate in feed for Nile tilapia Oreochromis niloticus - I Kadek Sumiana; Julie Ekasari; Dedi Jusadi; Mia Setiawati (Jurnal Akuakultur Indonesia)
ABSTRACT This study aimed to evaluate sago pulp fermentation method and its effect on crude fiber content, digestibility, and utilization of sago pulp as a feed raw material for Nile tilapia. Fermentation was done using three different fermenters, i.e. yeast tapai and baker’s yeast with five doses of 10 g/kg, 20 g/kg, 50 g/kg,70 g/kg,100 g/kg, respectively, and sheep rumen liquid with five doses of 100 mL/kg, 200 mL/kg, 300 mL/kg, 500 mL/kg and 1000 mL/kg. The incubation time was 0, 24, 72, and 96 hours. In the digestibility test, tilapia (25 g) was stocked at a density of 7 fish/aquarium. Three different diets were applied in quadruplicate, i.e. reference diet (100% reference diet), unfermented sago pulp (AS), and fermented sago pulp (ASF). Three different dietary treatments (in quadruplicate) containing different carbohydrate sources were tested, i.e. cassava flour as a comparion (G), unfermented sago pulp (AS), and fermented sago pulp (ASF). Fermentation of sago pulp with tapai yeast at a dose of 50 g/kg at 72 hours incubation time could reduce crude fiber by 35.76%, neutral detergent fiber (NDF) by 32.68%, and hemicellulose by 60.39%. Fermentation with yeast tapai could significantly increase sago pulp dry matter digestibility by 34% and carbohydrate digestibility by 21%, as well as increase glucose absorption. The growth experiment showed that the use of ASF diets resulted in higher specific growth rate (3.31 ± 0.12%/ day), protein retention (47.34 ± 5.23%) and fat retention (85.58 ± 5.44%) than those of AS dietary. In conclusion, fermentation of sago pulp using yeast tapai at a dose of 50 g/kg at 72 hours incubation could reduce crude fiber content and increase dry matter and carbohydrate digestibilities, so that it can be used as a source of carbohydrates in tilapia diet.